2017
DOI: 10.5152/turkpediatriars.2017.4982
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of burnout and job satisfaction levels in residents of pediatrics

Abstract: Aim: The aim of the study was to examine the level of job-related burnout and the level of job satisfaction among residents of pediatrics. Material and Methods:A total of 102 residents of pediatrics who were trained in two Ministry of Health teaching and research hospitals and in two university hospitals in Izmir were included in the study. Demographic data (age, sex), lifestyle (living with parents or not, marital status, number of children) and professional characteristics (total time spent in profession, ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
2
8
0
3
Order By: Relevance
“…According to the results of our study, the scores of the MBI subgroups decrease as the year of work increases in the profession. Similar to our study, some studies have reported that burnout decreases as the working year increases [31,32]. According to these results, we believe that the physicians have a lack of experience in dealing with stressor factors in the first years of their career.…”
Section: Discussionsupporting
confidence: 90%
“…According to the results of our study, the scores of the MBI subgroups decrease as the year of work increases in the profession. Similar to our study, some studies have reported that burnout decreases as the working year increases [31,32]. According to these results, we believe that the physicians have a lack of experience in dealing with stressor factors in the first years of their career.…”
Section: Discussionsupporting
confidence: 90%
“…In a study carried out with pediatric residents, with an average work period of 78 hours per week, it was identified that the level of depersonalization increased in the residents as the number of shifts increased [33].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a high number of shifts implies exhaustion and low job satisfaction [33,37]. The influence of organizational issues on the development of burnout has been tested worldwide, and there are associations between the syndrome and performance in sectors that attend traumatic situations, long and irregular work shifts [38], influence of sectors such as [39] and, more recently, the relationship between the disease and the patient's safety culture has been described [8].…”
Section: Discussionmentioning
confidence: 99%
“…Reports of a higher incidence of BS in residents and physicians with shorter professional experience were also published on other populations. This relationship applies to both surgical and non-surgical specialties [73][74][75]. However, Dyrbye et al conducted a survey in a large group of over 7000 doctors and found middle career (11-20 years in profession) to be particularly challenging time for doctors [76], also when analyzed by gender, specialty or setting.…”
Section: Professional Experience and Bs In Physiciansmentioning
confidence: 99%